Multiple organ failure : pathophysiology, prevention, and therapy - Baue, Arthur; Faist, Eugen; Fry, Donald E (Springer, 2000)
This text brings together international experts to explore the pathophysiology, prevention, and treatment of Systemic Inflammatory Response Syndrome, Multiple Organ Dysfunction Syndrome and Multiple Organ Failure with an emphasis on injury, inflammation, ischemia, and inflammation. Emphasizing material of clinical relevance to patient care, 75 chapters address development of SIRS, MODS and MOF including risk factors and history; mechanisms of SIRS and organ failure; mediators and effectors including cytokines, biologic control of inflammation, histamine, nitric oxide; prevention and general therapy including intensive care monitoring, surgical intervention and operating for trauma; specific remote organ failure including lungs, stomach, kidneys, liver and CNS; and a comprehensive summary of therapeutic horizons. Generously illustrated with more than 300 drawings, photographs and tables, this text is an invaluable resource for general surgeons, critical and intensive care specialists, traumatologists, pulmonologists, and infectious disease experts.
Keywords: patologie; fyziologie; farmakologie; anesteziologie a intenzivní lékařství; syndrom systémové zánětlivé reakce; Pharmacology; Terminology as Topic; Systemic Inflammatory Response Syndrome; multiorgánové selhání; terminologie jako téma; Multiple Organ Failure